Organoid development and applications in gynecological cancers: the new stage of tumor treatment - Yang Li; Meiying Qin; Ning Liu; Chunmei Zhang (Journal of Nanobiotechnology)
Abstract Gynecologic cancers (GCs), including cervical cancer (CC), ovarian cancer (OC), endometrial cancer (EC), as well as vulvar and vaginal cancers, represent major health threats to women, with increasing incidence rates observed globally. Conventional treatments, such as surgery, radiation therapy, and chemotherapy, are often hindered by challenges such as drug resistance and recurrence, contributing to high mortality rates. Organoid technology has emerged as a transformative tool in cancer research, offering in vitro models that closely replicate the tumor cell architecture and heterogeneity of primary cancers. Tumor-derived organoids preserve the histological and molecular characteristics of the original tumors, making them invaluable for studying tumor biology, molecular pathways, and the tumor immune microenvironment. Furthermore, organoids play a crucial role in biomarker discovery, drug screening, and the development of personalized therapeutic strategies. In contrast to traditional cell lines and patient-derived xenograft (PDX) models, gynecologic cancer organoids accurately mirror the genetic mutations and specific gene expression profiles of primary tumors. This review provides an overview of recent advancements in the development of gynecologic cancer organoid models, highlighting their contributions to understanding disease mechanisms, facilitating drug discovery, and advancing precision medicine. It also addresses the potential and challenges of organoid technology, with a focus on its role in advancing personalized treatment approaches for GCs. Graphical abstract